2023
DOI: 10.1186/s40795-023-00755-4
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic index, glycemic load, dietary insulin index, and dietary insulin load in relation to cardiometabolic risk factors among participants with atherosclerosis: a cross-sectional study

Hossein Bavi Behbahani,
Mahshad Shokuhi,
Cain C. T. Clark
et al.

Abstract: Background We examined the cross-sectional associations of dietary Glycemic Index (GI), Glycemic Load (GL), Dietary Insulin Index (DII), and Dietary Insulin Load (DIL) with cardiovascular disease (CVD) factors in subjects with atherosclerosis. Methods The present cross-sectional study was conducted on subjects with atherosclerosis. Regular dietary intake was assessed using a 168-item semi-quantitative food frequency questionnaire (FFQ) and GI, GL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Body Mass Index (BMI) was calculated using the formula: weight in kilograms divided by the square of height in meters. Waist circumference (WC) was measured at the narrowest point of the torso with a precision of 0.5 cm, while hip circumference (HC) was assessed at the most prominent part of the hip area using a tape measure 56 58 . Waist-to-hip ratio (WHR) was computed by dividing WC by HC.…”
Section: Methodsmentioning
confidence: 99%
“…Body Mass Index (BMI) was calculated using the formula: weight in kilograms divided by the square of height in meters. Waist circumference (WC) was measured at the narrowest point of the torso with a precision of 0.5 cm, while hip circumference (HC) was assessed at the most prominent part of the hip area using a tape measure 56 58 . Waist-to-hip ratio (WHR) was computed by dividing WC by HC.…”
Section: Methodsmentioning
confidence: 99%
“…Odds ratios for Q2 (OR, 0.22; 95% CI [0.06–0.81]), Q3 (OR, 0.23; 95% CI [0.06–0.85]), and Q4 (OR, 0.25; 95% CI [0.07–0.95]) showed relationships between DGI and obesity in the present study. A recent previous study showed an association between DGL and an increased likelihood of obesity in women, while no such association was found in men among participants with atherosclerosis ( Behbahani et al, 2023 ).…”
Section: Discussionmentioning
confidence: 92%
“…The dietary insulin index (DII) and dietary insulin load (DIL) represent dynamic parameters that reflect the postprandial insulin response to foods that consumed ( Behbahani et al, 2023 ). The DII is defined as a direct measure of the postprandial insulin response to a test food, comparing it to an isoenergetic portion of a reference food (similar to the glycemic index, using either glucose or white bread).…”
Section: Introductionmentioning
confidence: 99%